FOXA3, a Negative Regulator of Nur77 Expression and Activity in Testicular Steroidogenesis - Hansle Kim; Sudeep Kumar; Keesook Lee (International Journal of Endocrinology)
Biosynthesis of testosterone occurs mainly in the testicular Leydig cells. Nur77, an orphan nuclear receptor that is expressed in response to the luteinizing hormone/cyclic adenosine monophosphate (LH/cAMP) signaling pathway, is one of the key factors that regulate steroidogenesis in Leydig cells. The function of Nur77 is modulated through interaction with other proteins. FOXA3, a transcription factor that is crucial for male fertility, is also expressed in Leydig cells. Here, we sought to elucidate the role of FOXA3 in testicular steroidogenesis by focusing on its interaction with Nur77. LH/cAMP signaling induces the onset of steroidogenesis in Leydig cells but has a repressive effect on the expression of FOXA3. Overexpression of FOXA3 in MA-10 Leydig cells repressed cAMP-induced expression of Nur77 and its target steroidogenic genes (StAR, P450c17, and Hsd3β). Furthermore, FOXA3 suppressed Nur77 transactivation of the promoter of steroidogenic genes. In mouse primary Leydig cells, adenovirus-mediated overexpression of FOXA3 had similar effects and resulted in decreased production of testosterone. Taken together, these results suggest the role of FOXA3 in the regulation of steroidogenic genes in Leydig cells and fine-tuning steroidogenesis in the testis.